(untitled) (Legal journal - Research in Legal and Social Sciences, 2025)
t The aim of this research is to analyze the current criminal procedural legislation and to propose the admission of testimony given in advance of trial, with full evidentiary value, from children and adolescents who may be victims of criminal offenses of any kind. Among the findings, it is highlighted that the information or testimony these minors may provide could be crucial for clarifying the facts under investigation. However, considering that the victims are particularly vulnerable individuals, it is essential that such investigative procedures be carried out in a manner that prevents further harm or suffering beyond that already caused by the offense itself. The proposal focuses on preventing secondary victimization and preserving evidence. The research follows a documentary method, with a qualitative approach, non-experimental design, and descriptive scope. As a technique, it relies on the collection of instrumental data through the review of legal frameworks from other countries and related legal doctrines. The study concludes that the legislative possibility of anticipated evidentiary measures is provided for in Article 320 of the Code of Criminal Procedure. In other words, it is legally feasible for evidence to be produced before the trial phase under certain conditions. Within the hypotheses contemplated by this provision, it is also possible to include the testimony of the child victim, in order to avoid secondary victimization resulting from their contact with the criminal process and to preserve the integrity of the evidence